Modelling of a radio frequency plasma bridge neutralizer (RFPBN). (2017) - Scholze, F.; Eichhorn, C.; Bundesmann, C.; Spemann, D.; Neumann, H.; Bulit, A.; Feili, D.; Amo, J. Gonzalez del
Abstract: A performance model of a radio frequency plasma bridge neutralizer was developed to calculate the electrical parameters and optimize the neutralizer design. Minimization of power losses and gas consumption, and a maximization of the neutralizer lifetime and the reliability of the system are requirements of all electric propulsion concepts and strongly determine their future application. The requirements of the neutralizer depend on mission profiles.